Effect of Administration of Combination of Captopril and Celery Extract on Blood Pressure and Electrolyte Levels of Hypertensive Rats - Siska Siska; Franciscus D. Suyatna; Abdul Mun'im; Anton Bahtiar (Indonesian Journal of Pharmaceutical Science and Technology, 2020)
Based on previous reports, the combination of captopril and celery could reduce blood pressure in hypertensive patients. This study aimed to investigate the changes of blood pressure, urine volume, sodium, and potassium level, due to concomitant administration of captopril with celery extract orally in male rats induced by 4% NaCl. The blood pressure was measured using a non-invasive tail method. The urine and blood were collected, and the sodium, potassium concentration, and cumulative urine volume were measured. The combination of 5 mg/kgBW of captopril and 40 mg/kgBW of celery extract decreased the blood pressure in hypertensive rats better than 5 mg/kgBW of captopril alone. The fell in blood pressure was followed by an increase in urine volume. Urinary and serum sodium, serum potassium levels tended to increase in all treatment groups, but not significantly different from the healthy group. Urinary potassium levels tended to decrease except in the combined 5 mg/kgBW of captopril and 40 mg/kgBW of celery extract. In conclusion, oral administration of a combination of 5 mg/kgBW captopril and 40 mg/kgBW celery extract decreased the blood pressure to the standard value in NaCl-induced hypertension rats.Keywords: Apium graveolens, captopril, celery, hypertension, pharmacodynamic